Effects of resveratrol on renal ischemia-reperfusion injury: A systematic review and meta-analysis - Lan, Tian-ying; Dun, Rong-liang; Yao, Dong-sheng; Wu, Feng; Qian, Yi-ling; Zhou, Yuan; Zhan, Tian-tian; Shao, Ming-hai; Gao, Jian-dong; Wang, Chen (Frontiers in Nutrition, 2023)
Renal ischemia-reperfusion (I/R) injury may lead to acute kidney injury, which is characterized by high morbidity and mortality rates. Resveratrol (RSV) can be extracted from Chinese herbs, and multiple animal experiments have demonstrated its potential for renal protection. This systematic review evaluates the protective effect of RSV against renal I/R injury in animal models. The PubMed, Embase, Web of Science, and Science Direct databases were searched for animal experiments related to RSV in renal I/R injury from their establishment to June 2022. In total, 19 studies were included with 249 animals (129 treated with RSV and 120 as controls). The pooled analysis revealed that RSV administration significantly decreased serum creatinine (SCr) levels (16 studies, n = 243, WMD = -58.13, 95% CI = -79.26 to -37.00, p < 0.00001) and blood urea nitrogen (BUN) levels (12 studies, n = 163, WMD = -34.37, 95% CI = -46.70 to -22.03, p < 0.00001) in the renal I/R injury model. The level of malondialdehyde (MDA), an oxidative stress index, was alleviated (7 studies, n = 106, standardized mean difference (SMD) = -6.05, 95% CI = -8.90 to -3.21, p < 0.0001) and antioxidant enzymes such as glutathione (GSH) (7 studies, n = 115, SMD = 9.25, 95% CI = 5.51 to 13.00, p < 0.00001) and catalase (CAT) (4 studies, n = 59, SMD = 8.69, 95% CI = 4.35 to 13.03, p < 0.0001) were increased after treatment of RSV. The subgroup analysis suggested that 5 to 10 mg/kg of RSV optimally protects against renal I/R injury as both the BUN and SCr levels were significantly decreased at this dosage. The protective effects of RSV against renal I/R injury might be attributed to multiple mechanisms, such as inhibiting oxidative stress, apoptosis, inflammation, fibrillation and promoting autophagy. For a deeper understanding of the protective effects of RSV, experimental studies on animal models and large randomized controlled trials in humans are needed.